Wolfhard Janke turns 60 (Condensed Matter Physics, 2015)
On December 11th, 2015, Wolfhard Janke, a member of the Editorial Board of ``Condensed Matter Physics'' and a leading expert in computer simulations in condensed matter physics, celebrated his 60th birthday.